2012
DOI: 10.1186/ar3875
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the role of endosomal Toll-like receptors in murine collagen-induced arthritis reveals a potential role for TLR7 in disease maintenance

Abstract: IntroductionEndosomal toll-like receptors (TLRs) have recently emerged as potential contributors to the inflammation observed in human and rodent models of rheumatoid arthritis (RA). This study aims to evaluate the role of endosomal TLRs and in particular TLR7 in the murine collagen induced arthritis (CIA) model.MethodsCIA was induced by injection of collagen in complete Freund's adjuvant. To investigate the effect of endosomal TLRs in the CIA model, mianserin was administered daily from the day of disease ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 47 publications
6
33
0
1
Order By: Relevance
“…TLRs 7 and 8 respond to ssRNA. Genetic deletion of murine TLR7, which is comparable to human TLR8 (huTLR8), has been shown to decrease RA disease parameters, such as inflammation 32. Accurate murine models of TLR8 have proven somewhat difficult as murine TLR8 does not recognize the same ligands as huTLR8 due to a sequence difference of five amino acids.…”
Section: Tlrs In Ramentioning
confidence: 99%
“…TLRs 7 and 8 respond to ssRNA. Genetic deletion of murine TLR7, which is comparable to human TLR8 (huTLR8), has been shown to decrease RA disease parameters, such as inflammation 32. Accurate murine models of TLR8 have proven somewhat difficult as murine TLR8 does not recognize the same ligands as huTLR8 due to a sequence difference of five amino acids.…”
Section: Tlrs In Ramentioning
confidence: 99%
“…In previous studies, we had identified a role for TLRs and, in particular, TLR8 in the production of spontaneous TNF in human RA synovial membrane cultures (32,42).…”
Section: Resultsmentioning
confidence: 99%
“…Although TLR7 -/-CIA model and WT mice developed RA with a similar frequency, TLR7 -/-CIA model was characterized by a decrease in paw swelling, number of paws affected and clinical score than WT mice [115]. Accordingly, an amelioration of RA symptoms was observed after intra-articular TLR7 knockdown in rat CIA model [116].…”
Section: Rheumatoid Arthritismentioning
confidence: 95%